2023
DOI: 10.3390/ijms242216311
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of ovary serine protease Leads to Ovary Deformation and Female Sterility in the Asian Corn Borer, Ostrinia furnacalis

Porui Zhang,
Zuerdong Jialaliding,
Junwen Gu
et al.

Abstract: Oogenesis in insects is a carefully orchestrated process, facilitating the formation of female gametes, which is regulated by multiple extrinsic and intrinsic factors, including ovary serine protease (Osp). As a member of the serine protease family, Osp is a homolog of Nudel, a maternally required protease defining embryonic dorsoventral polarity in Drosophila. In this study, we used CRISPR/Cas9-mediated mutagenesis to functionally characterize Osp in the Asian corn borer, Ostrinia furnacalis, a devastating ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Moreover, the amino acid sequence of PxOsp shares almost 50% similarity with B. mori, S. liturs, and O. furnacalis, indicating that Osp homologous are highly conserved in lepidopteran insects and present in almost all insect species. 23,24,[48][49][50] The stage-specific expressions of the PxOsp gene showed an increasing trend from the pupal stage and peaked at the adult stage. The relative expression levels of PxOsp exhibited at least a 10-fold increase in female adults compared to other developmental stages (from egg to pupae).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the amino acid sequence of PxOsp shares almost 50% similarity with B. mori, S. liturs, and O. furnacalis, indicating that Osp homologous are highly conserved in lepidopteran insects and present in almost all insect species. 23,24,[48][49][50] The stage-specific expressions of the PxOsp gene showed an increasing trend from the pupal stage and peaked at the adult stage. The relative expression levels of PxOsp exhibited at least a 10-fold increase in female adults compared to other developmental stages (from egg to pupae).…”
Section: Discussionmentioning
confidence: 99%
“…This expression pattern of PxOsp is almost synchronized with the Osp expression patterns of other lepidopteran insects such as B. mori, S. litura, and O. furnacalis. 23,24 The tissue-specific expression profile revealed that PxOsp exhibited nearly 270-fold higher expression in the ovaries of adult females compared to other tissues, indicating its specificity for ovary development. Similar expression profiles are also observed in other insect species, such as Nilaparvata lugens, Pteromalus puparum, O. furnacalis, B. mori, and S. litura.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations